Support for the hypothesis that growth of eastern Baltic cod is affected by mild hypoxia. A comment on Svedäng et al. (2022). (20th April 2022) - Brander, Keith
Abstract: Stock biomass and size composition of eastern Baltic cod (EBC) has declined, with low recent stock productivity attributed to loss of major spawning areas, reduced growth rates, and possibly increased natural mortality. Svedäng et al . present valuable new data for evaluating the causes of these changes. However, contrary to their own conclusions, those new data actually provide both direct and indirect support for the hypothesis that the reduced growth rate observed may be due to a decline in ambient oxygen for small cod in the Bornholm Basin area (SD25). Their long time series of reproductive volume (RV) extends our knowledge of historic changes in the limits to spawning imposed by salinity and oxygen. However, the causes and consequences of such spawning area changes are well established. Therefore, this Comment only addresses the contentious debate about causes of decline in growth.